The morphometric description of the thoracic and lumbar vertebral pedicles in European, African and mixed population of South Africa - Sani, Hassan Yauri (My University, 2018)
The use of pedicle screws fixation for surgical management of spinal disorders has become increasingly popular worldwide. Segmental pedicle screw fixations are used in spinal canal decompression surgery for various spine disorders such as scoliosis, spondylolisthesis, fractures, tumor and iatrogenic or degenerative instability. The main challenge to the use of pedicle screw can be due to mismatched size of the screw and the pedicle. This may result in cortical perforation of the pedicle or fracture of the pedicle. Understanding of pedicle morphometric values is important in designing pedicle screw systems as well as in accurately placing the screws to avoid or minimize complications. Most of the studies on the morphometry of the vertebral pedicles have been reported in the European populations, with a few reports in Asian populations and none in the African populations. Previous studies have shown significant population and ethnic differences in pedicle morphometry. The current study presents information on the thoracic and lumbar pedicle dimensions at the isthmus in the European, African and Mixed-ancestry populations of South Africa. The study utilized thoracic and lumbar vertebrae of 60 African, 60 European and 54 Mixed ancestry adult human populations of South Africa with equal male to female representation. The dry human skeletons used were obtained from the Raymond A. Dart Collection of Human specimens housed in the School of Anatomical Sciences at the University of the Witwatersrand. Pedicles of the vertebrae were assessed and measured. The external measurements on the isthmus of the pedicle were performed using a digital Vernier caliper (accuracy, 0.1 mm) on the right and left pedicles. The angular measurements were performed with a standard goniometer (accuracy of 1°). The measurements taken at the isthmus of the vertebral pedicle included the pedicle width, pedicle height, transverse angle, sagittal angle, chord length and inter-pedicular distance. For the internal measurement, all the vertebrae were radiograph and the transverse (width) and vertical (height) inner cortical diameters were measured at the isthmus of the pedicle using image processing software (image J®). In the three populations of South Africa, the mean pedicle width was found to gradually decrease from vertebral levels T1 to T5 and then gradually increased to vertebral level T12 in the thoracic spine whereas in the lumbar spine, the mean pedicle width gradually increased from vertebral levels L1 to L5. The mean pedicle height gradually increased from T1 to T12 in the thoracic spine and in the lumbar spine it gradually decreased from L1 to L5. The mean transverse angle gradually decreases from vertebral levels T1 to T8 and then increased gradually to vertebral level T12 in the thoracic spine, and in the lumbar spine, it increased gradually from vertebral levels L1 to L5. The mean sagittal angle marginally decreased from vertebral levels T1 to T7 and then increased to vertebral level T12 in the thoracic spine, and in the lumbar spine it slightly increased from vertebral levels L1 to L5. The mean chord length gradually increased from vertebral levels T1 to T12 in the thoracic spine, while in the lumbar spine it gradually increased from vertebral levels L1 to L3 and then slightly decreased from level L4 to L5. The mean inter-pedicular distance was found to gradually decrease from vertebral levels T1 to T6 then gradually increased to vertebral level T12 in the thoracic spine, and in the lumbar spine, the mean inter-pedicular distance gradually increased from vertebral levels L1 to L5. The mean transverse inner cortical diameter gradually decreased from vertebral levels T1 to T5 and then gradually increased to vertebral level T12 in thoracic spine, and in the lumbar spine; it gradually increased from vertebral levels L1 to L5. The mean vertical inner cortical diameter gradually increase from vertebral levels T1 to T12 in the thoracic spine whereas in the lumbar spine it gradually decrease from L1 to L5.
A Dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Medicine, 2018
Keywords: Spinal Diseases; Lumbar Vertebrae; Thoracic Vertebrae